Keberlanjutan UMKM Ditinjau Dari Digitalisasi UMKM, Financial Literacy, Dan Behaviour Financial - Suleman, Nurjana; K. Thalib, Maryati (Universitas Gorontalo, 2024)
This study aims to examine the influence of MSME Digitalization, Financial Literacy, and Behavioral Finance on the sustainability of MSMEs in Gorontal City. This type of research is research quantitatively using regression analysis methods multiplex with the SPSS 25 program. Retrieval technique samples using the cluster method. Data collection was carried out through a survey method using a questionnaire distributed directly to 99 MSME actors in the central city of Gorontalo City. The results of this study show that the Digitalization of MSMEs has a significant effect on the Sustainability of MSMEs of 3,694, Financial Literacy has no significant effectto the MSME Sustainability Tax of 1,663, Behavior Financial has a significant effect on the MSME sustainability Tax of 3,632. simultaneously Digitalization of UMKM, Financial Literacy, and Financial Behavior has a significant effect on MSME Sustainability of 11,294.